Parent-Child Engagement in Decision Making and the Development of Adolescent Affective Decision Capacity and Binge Drinking - Xiao, Lin (2011)
The goal of this study was to investigate how parents’ engagement of their child in everyday decision-making influenced their adolescent’s development on two neuropsychological functions, namely, affective decision-making and working memory, and its effect on adolescent binge-drinking behavior. We conducted a longitudinal study of 192 Chinese adolescents. In 10(th) grade, the adolescents were tested for their affective decision-making ability using the Iowa Gambling Task (IGT) and working memory capacity using the Self-ordered Pointing Test (SOPT). Questionnaires were used to assess perceived parent-child engagement in decision-making, academic performance and drinking behavior. At one-year follow-up, the same neuropsychological tasks and questionnaires were repeated. Results indicate that working memory and academic performance were uninfluenced by parent-child engagement in decision-making. However, compared to adolescents whose parents made solitary decisions for them, adolescents engaged in everyday decision-making showed significant improvement on affective decision capacity and significantly less binge-drinking one year later. These findings suggest that parental engagement of children in everyday decision-making might foster the development of neurocognitive functioning relative to affective decision-making and reduce adolescent substance use behaviors.